2007
DOI: 10.1002/cncr.23156
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in colorectal cancer screening practices and knowledge within a low‐income population

Abstract: Chondroitin sulfate proteoglycans (CSPGs) play a pivotal role in many neuronal growth mechanisms including axon guidance and the modulation of repair processes following injury to the spinal cord or brain. Many actions of CSPGs in the central nervous system (CNS) are governed by the specific sulfation pattern on the glycosaminoglycan (GAG) chains attached to CSPG core proteins. To elucidate the role of CSPGs and sulfated GAG chains following traumatic brain injury (TBI), controlled cortical impact injury of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 71 publications
6
58
0
Order By: Relevance
“…No racial difference was observed in the percentage of people with a positive FOBT who underwent a colonoscopy in the following 1 2 m o [ 3 5 ] . A s t u d y a m o n g l ow i n c o m e wo m e n showed that African-American descent predicts a lower likelihood of reporting having had screening colonoscopy within the past 10 years (OR = 0.46, P < 0.001) although following the screening guidelines did not vary by race [36] .…”
Section: Screeningmentioning
confidence: 98%
“…No racial difference was observed in the percentage of people with a positive FOBT who underwent a colonoscopy in the following 1 2 m o [ 3 5 ] . A s t u d y a m o n g l ow i n c o m e wo m e n showed that African-American descent predicts a lower likelihood of reporting having had screening colonoscopy within the past 10 years (OR = 0.46, P < 0.001) although following the screening guidelines did not vary by race [36] .…”
Section: Screeningmentioning
confidence: 98%
“…Cognitive factors such as knowledge and beliefs about the outcomes associated with CRC screening and the desirability or undesirability of those outcomes (i.e., attitudes toward screening), and perceptions about one's ability (or self efficacy) to engage in screening, will influence CRC screening adherence by shaping motivation to be screened. These cognitive factors have been shown to vary by race [35][36][37][38][39][40][41] and hence, may contribute to racial differences in CRCS. The framework assumes that medical and social environmental factors can affect adherence by determining whether an individual has access to screening (i.e., is offered a screening procedure and resources for conducting the procedure are locally available) or by influencing the accessibility of screening (by determining the availability of things such as transportation to and from a colonoscopy appointment).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…While only a few of our respondents may be familiar with specific cancer statistics on survival for African American women, 4 our data suggest that many African American women in South Los Angeles believe that there are differences in survival rates for breast, cervical, and colorectal cancer. Since beliefs and perceptions are often shaped by events in individuals' environment, 24 this awareness may be influenced by cancer outcomes that women observe in their community.…”
Section: Discussionmentioning
confidence: 78%
“…2 Not all women are aware of these screening guidelines. 3,4 However, a woman's belief regarding the benefits of screening is a construct that is included in many health behavior theories, including the Health Belief Model, Social Cognitive Theory, and the Health Behavior Framework. [5][6][7] This construct, also labeled ''perceived efficacy of early detection'' or ''perceived benefits of screening,'' has been discussed in the literature and particularly in studies with minority women in connection with fatalism.…”
Section: Introductionmentioning
confidence: 99%